TiO2-Cu photocatalysts: A study on the long- and short-range chemical environment of the dopant - Carvalho, Hudson W. P.; Rocha, Marcus V. J.; Hammer, Peter [UNESP]; Ramalho, Teodorico C. (My University, 2013)
In this study, the short- and long-range chemical environments of Cu dopant in TiO2 photocatalyst have been investigated. The Cu-doped and undoped TiO2 specimens were prepared by the sol-gel approach employing CuSO4·5H2O and Ti(O-iPr)4 precursors and subjecting the dried gels to thermal treatment at 400 and 500 C. The photocatalytic activity, investigated by methylene blue degradation under sunlight irradiation, showed a significantly higher efficiency of Cu-doped samples than that of pure TiO2. The X-ray diffraction results showed the presence of anatase phase for samples prepared at 400 and 500 C. No crystalline CuSO4 phase was detected below 500 C. It was also found that doping decreases the crystallite size in the (004) and (101) directions. Infrared spectroscopy results indicated that the chemical environment of sulfate changes as a function of thermal treatment, and UV-vis spectra showed that the band gap decreases with thermal treatment and Cu doping, showing the lowest value for the 400 C sample. X-ray absorption fine structure measurements and analysis refinements revealed that even after thermal treatment and photocatalytic assays, the Cu2+ local order is similar to that of CuSO4, containing, however, oxygen vacancies. X-ray photoelectron spectroscopy data, limited to the near surface region of the catalyst, evidenced, besides CuSO4, the presence of Cu1+ and CuO phases, indicating the active role of Cu in the TiO2 lattice. © 2013 Springer Science+Business Media New York.
Keywords: Chemical environment; Higher efficiency; Methylene blue degradations; Near surface regions; Photocatalytic activities; Sol-gel approach; Sunlight irradiation; X ray absorption fine structures; Aromatic compounds; Copper; Degradation; Heat treatment; Infrared spectroscopy; Photocatalysts; Photoelectrons; X ray diffraction; X ray photoelectron spectroscopy; Titanium dioxide